PERANAN BUDAYA MUTU SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN SMA NEGERI 2 CEPU - NURLAELA NURLAELA; NOOR MIYONO; TITIK HARYATI (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2023)
School culture is expected to be able to improve the quality of the school, and the character of all school members, principals, teachers, education staff, students and residents at the school. A good school culture and habituation to daily practices at school is expected to provide opportunities for school residents to work optimally, efficiently and energetically, and with high enthusiasm to continue to grow and develop into good individuals. This research aims to explore more deeply the role of school culture in improving the quality of education. With a better understanding of how school culture influences the learning process and can identify strategies and best practices that can be implemented in schools to improve the quality of education at SMA Negeri 2 Cepu. The method used is qualitative with data sources from interviews, observations and document data using triagulation data validation. The results of the research show that the most prominent school culture is the culture of literacy by creating a reading corner in the corner of the library by offering a collection of the latest books, making media for each class and media in the school, this can realize the character of the Pancasila student profile of mutual cooperation, critical reasoning, innovation and independent. A culture of environmental cleanliness by sorting waste according to its type and making compost from dry leaves and organic waste. This can create the profile character of a Pancasila student who is devoted to God, the One and Only, has noble character, is cooperative, and innovative. independent and critical thinking. All of this can be realized because of the good management of the principal in realizing the vision and mission of the school and the participation of teachers, education staff, parents and students. as well as the entire school community. So that the school succeeded in becoming an adiwiyata school. ABSTRAKBudaya sekolah diharapkan mampu memperbaiki mutu sekolah, dan karakter seluruh warga sekolah kepala sekolah, guru, tenaga kependidikan, peserta didik dan warga di sekolah. Budaya sekolah yang baik dan menjadi pembiasaan praktik sehari-hari di sekolah diharapkan memberikan peluang warga sekolah dapat bekerja secara optimal, efisien dan energik, dan semangat tinggi untuk terus tumbuh dan berkembang menjadi pribadi-pribadi yang baik. Penelitian ini bertujuan untuk menggali lebih dalam peranan budaya sekolah dalam meningkatkan mutu pendidikan. Dengan pemahaman yang lebih baik tentang bagaimana budaya sekolah mempengaruhi proses pembelajaran dan dapat mengidentifikasi strategi dan praktik terbaik yang dapat diterapkan di sekolah-sekolah untuk meningkatkan kualitas pendidikan di SMA Negeri 2 Cepu. Metode yang digunakan kualitatif dengan sumber data dari hasil wawancara, pengamatan dan data dokumen dengan menggunakan validasi data triagulasi. Hasil penelitian menunjukkan budaya sekolah yang paling menonjol adalah budaya literasi dengan membuat pojok baca disudut perpustakaan dengan menawarkan koleksi buku-buku terbaru, pembuatan mading setiap kelas dan mading di sekolah, hal ini dapat mewujudkan karakter profil pelajar pancasila gotong royong, bernalar kritis, inovatif dan mandiri. Budaya kebersihan lingkungan dengan memilah sampah sesuai dengan jenisnya dan pembuatan pupuk kompos dari daun-daun kering dan sampah organik. Hal ini dapat mewujudkan karakter profil pelajar pancasila bertakwa kepada Tuhan Yang Masa Esa dan berakhlak mulia, gotomg rorong, inovatif. mandiri dan berpikir kritis. Semua ini dapat terwujud karena manajemen kepala sekolah yang baik dalam mewujudkan visi dan misi sekolah dan peran serta guru, tenaga pendidikan, orang tua, peserta didik. serta seluruh warga sekolah. Sehingga sekolah berhasil menjadi sekolah adiwiyata.